(untitled) (Global Journal of Human-Social Science, 2019)
This research aims to discuss how a selfie produces meaning for and through subjects. It is already known that the selfie is an image, and not an oral or written production, but we comprehend that, according to the Discourse Analysis theoretical field, it seeks to comprehend the workings and the production of meaning, considering the constitutive relationship between language, subject and history. Just as with words do not originate in us, since we just reproduce and re-signify them, it is no different with the selfie’s discursive gesture. There is a discursive memory in looking at oneself in order to capture one’s image, be it on screen or through their smartphone. The ritual of the self-portrait is sustained by and in this memory. A process of resignificance of the practice of self-registry determines the selfie’s productions of meaning, which relates to the ideological conjuncture of the production conditions of the digital discourse. Furthermore, we present how the social networks call on the subjects for massive productions of selfies, in order to maintain their profiles in the limelight, through the ideological notion of consumption and circulation.